(untitled) (Journal of Hama University, 2022)
The research was conducted in the Taizin agricultural nursery in Hama Governorate, season 2021, to study the effect of the treatment of the cuttings of hazelnuts with two concentrations (10-20g/l) each of plant extracts (licorice, cinnamon, willow) at two concentrations each (10-10g/l), in addition to the control (treatment with IBA at a concentration of 3000 ppm). The results indicated that the licorice treatment at a concentration of 20g/l gave the best results in the rooted cuttings ratio, which amounted to 76.70%, while it was significantly superior to all treatments and the control in (root diameter, leaf area, leaf content of total chlorophyll, the dry weight of the planter) with an average of (2.90mm; 42.12cm²; 5.30mg/g; 6.95g) respectively. While the treatment of licorice 20g/l was superior to that of (licorice 10g/l, cinnamon 10g/l and willow with two concentrations (10-20g/l), and the control) in ( the length roots 35cm, the wet weight 2.83g, the dry weight of the roots 1.32g, the length of the planter 40.20cm, and the wet weight of the planter 11.30g,) and in the treatment of cinnamon and willow at a concentration of (20g/l) increased. The rooting percentage improved in the characteristics of the root and vegetative growth compared with the control.